Anopheline species composition and the 1014F-genotype in different ecological settings of Burkina Faso in relation to malaria transmission - Traoré, Alphonse (Malar J, 2019)
BACKGROUND: A three-year longitudinal study was conducted in four sentinel sites from different ecological settings in Burkina Faso, between 2008 and 2010 to identify longitudinal changes in insecticide resistance within Anopheles gambiae complex species based on larval collection. During this study, adult mosquitoes were also collected indoor and outdoor using several methods of collection. The present study reports the diversity of malaria vectors and the 1014F-genotype from this adult collection and investigates the association between this 1014F-genotype and sporozoite rate. METHODS: Adult mosquitoes were collected from July to August (corresponding to the start of rainy season) and October to November (corresponding to the end of rainy season) over 3 years (2008–2010) at four sites across the country, using pyrethrum spray catches (PSC), exit traps and pit shelters. Anopheles gambiae complex mosquitoes were identified to species and genotyped for the L1014F kdr mutation by PCR using genomic DNA. The circumsporozoite antigen of Plasmodium falciparum was detected in mosquitoes using sandwich ELISA. RESULTS: Overall 9212 anopheline mosquitoes were collected during the study period. Of those, 6767 mosquitoes were identified as Anopheles gambiae sensu lato (s.l.). Anopheles arabiensis, Anopheles coluzzii, Anopheles gambiae and or Anopheles funestus were incriminated as vectors of P. falciparum in the study area with an average sporozoite rate of 5%, (95% CI 4.14–5.99%). The kdr1014F-genotype frequencies were 11.44% (95% CI 2.5–39.85%), 19.2% (95% CI 4.53–53.73%) and 89.9 (95% CI 63.14–97.45%), respectively for An. arabiensis, An. coluzzii and An. gambiae. The proportion of the 1014F-genotype varied between sporozoite-infected and uninfected An. gambiae s.l. group. There was no significant difference in the 1014F-genotype frequency between infected and uninfected mosquitoes. CONCLUSION: The current study shows the diversity of malaria vectors and significant interaction between species composition and kdr1014F-genotype in An. gambiae complex mosquitoes from Burkina Faso. In this study, no associations were found between the 1014F-genotype and P. falciparum infection in the major malaria vector An. gambiae s.l. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12936-019-2789-8) contains supplementary material, which is available to authorized users.